Qisas in the Crime of Murder: A Comparison of Islamic Criminal Law and the Criminal Code - Kamaluddin Pane; Mhd Yadi Harahap (Jurnal Cendikia ISNU SU, 2026)
The crime of murder is the most serious crime because it directly deprives people of the right to life, thus demanding a penal system that not only provides legal certainty, but also substantive justice. Islamic criminal law through the concepts of qisās and diyat offers a model of punishment that balances retributive justice, humanity, and welfare, by giving a central role to the victim's family. Meanwhile, the Indonesian Criminal Code, both in its old form and through Law No. 1 of 2023, places murder as a crime against the state with a penal approach that is increasingly shifting towards corrective and rehabilitative, especially through the provision of the conditional death penalty. This study aims to analyze and compare the concept of qisās in Islamic criminal law with the regulation of the crime of murder in the Indonesian Criminal Code in order to find common points and fundamental differences in the paradigm of justice adhered to. The research method used is normative legal research with legislative, conceptual, and comparative legal approaches, through literature studies on sources of Islamic law and positive law. The results of the discussion showed that Islamic criminal law emphasizes commensurate justice and the right to forgiveness of victims as a mechanism of social control, while the Criminal Code emphasizes the dominance of the state in criminalization with limited space for the role of the victim. In conclusion, this comparison shows that the values of justice in qisās have conceptual relevance to enrich the development of a national criminal law that is more just, humane, and responsive to the interests of victims without neglecting the principle of the rule of law.